ANALISIS PERBANDINGAN PENERIMAAN PAJAK PENGHASILAN SEBELUM DAN SESUDAH PENERAPAN TARIF TUNGGAL DAN PENGARUHNYA TERHADAP PAJAK PENGHASILAN TERUTANG (STUDI EMPIRIS PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT DI BURSA EFEK INDONESIA) (Jurnal Tepak Manajemen Bisnis, 2014)
This study was conducted to analyze the ratio of income tax revenue before and after the applicationof flat rate and the effect of change in tax rate on income tax due in oil palm sector in Indonesia Stock Exchangein 2007-2010. This study aims to determine the income tax revenue before flat rate, income tax revenue after a flatrate, whether there are differences in income tax revenue before and after the flat rate , and the effect of changesin the rate of income tax payable. The method used in this study is the method of independent sample t test tocompare the income tax revenue before and after the application of flat rate. Then proceed with regressionanalysis to see the effect of changes in tax rates on income tax due. The results showed an increase in income taxrevenue in 2007 and 2008 amounting to Rp2,149 billion. This increase was influenced by sunset policy (removalfacilities tax penalties). Income Tax Receipts after application of flat rate is analyzed, namely in 2009, 2010,2011 and 2012. Income tax revenue increased to Rp30 billion in 2009, but in 2010 decreased by Rp758 billion,in 2011 again increased by Rp508 billion in 2012 and an increase of Rp461 billion. This is of course influencedby changes in the rates used. With the use of flat rate tax payers do not have to go through several layers of therates adjusted by the amount of taxable income to calculate income tax due. So that taxpayers get the convenienceand practicality that is expected to increase income tax revenue . The amount of taxes received prior to theapplication of flat rate would average Rp2.377,81 billion increased to Rp3.283,75 billion after the applicationof flat rate, an increase in income tax revenue amounting to Rp90,59 billion. Effect of change in tax rate to theincome tax payable 0,000 is significantly smaller than 0.05 and the R value of 0,877. This is in accordance withprogram changes that are expected to increase the rate of income tax revenue.Keywords: Income Tax Revenue, Tax Rate, Income Tax Due